Power efficient, low loss and ultra-high isolation RF MEMS switch dedicated for antenna switch applications. (November 2017) - Mirzajani, Hadi; Ilkhechi, Afshin Kashani; Zolfaghari, Parviz; Azadbakht, Mostafa; Aghdam, Esmaeil Najafi; Ghavifekr, Habib Badri
Abstract: We present a new ultra-high isolation RF MEMS latching switch with ultra-low power consumption dedicated to antenna switch applications in multiband and multi-standard transceivers. Power management of the switch is done by integrating latching actuators in switch structure. Actuation voltage of the switch is 5 V and the switch consumes a power of around 131 mW for 50 µs while transition to ON or Deep-OFF states. The switch is modeled and its operation is comprehensively analyzed. The switch has an IIP3 of 127 dBm and power handling of up-to 6 W without causing stiction. The insertion loss of the switch is −0.5 dB up to 20 GHz. When the switch is OFF, the input and output are isolated with −50 dB for up to 20 GHz. At the Deep-OFF state, the switch is connected to the GND and isolation reaches −130 dB up to 20 GHz. These results are from FEM simulations and has not been verified by experiment. Graphical abstract: We present a new ultra-high isolation RF MEMS latching switch with ultra-low power consumption dedicated to antenna switch applications in multiband and multi-standard transceivers. The power management of the switch is done by integrating latching actuators in the switch structure. The switch only consumes DC power while transition between operating states. In addition to ON and OFF states, the switch has also a Deep-OFF state for ultra-high isolation applications. Highlights: The overall power consumption of the switch is 131 mW for 50 µs. The isolation of the switch reached -130 dB up to 20 GHz in Deep-OFF state. The insertion loss decreased to -0.5 dB by using µelectro-thermal actuators. Equivalent circuit model is extracted and simulation results are validated. Results show an IIP3 of 127 dBm and power handling of up-to 6 W without stiction.